Comparison of Sleep Quality before and after Chemotherapy in Locally Advanced Nonsmall Cell Lung Cancer Patients: A Prospective Study - Belloumi, N. (Sleep Disord, 2020)
BACKGROUND: Preservation of sleep quality is a modifiable and treatable factor, which may enhance the patient's adherence to other supportive and palliative care procedures. The outcome of sleep disturbances in lung cancer patients before and after treatment aren't reported. The aim of this study was to investigate changes in sleep quality before and after chemotherapy in locally advanced or metastatic NSCLC patients. METHODS: It was a prospective study including 64 patients with stage III or IV nonsmall-cell lung cancer. Patients answered the Tunisian dialectal version of the following questionnaires: PSQI and QLQ-C30 in order to evaluate, respectively, the sleep quality and the quality of life. The assessments took place before chemotherapy and then repeated after the chemotherapy course was over. RESULTS: The mean age was 62.9 years. All patients were active smokers. Before chemotherapy, there were 10 patients (15%) with poor sleep quality. The most frequent complaints were daytime sleepiness (70%) and nocturnal arousals (100%). After chemotherapy, the mean PSQI score increased from 2.9 to 5.4, and 45% of all patients had poor sleep quality. Most frequent complaints were the extension of sleep latency (69%), daytime sleepiness (98%), and nocturnal arousals (100%). Predicting factors of sleep disturbance according to statistical univariate analysis were delayed diagnosis confirmation (p = 0.05), delayed treatment onset (p < 10(−3)), depressive mood (p = 0.001), and anxious mood (p = 0.001). Multivariate analysis had shown a significant and independent correlation between sleep quality and shortened diagnosis and treatment delays. Sociodemographic parameters, clinical parameters, and factors related to treatment procedure had no correlation with sleep quality. CONCLUSIONS: Our study demonstrates the persistence and potential intensity worsening of sleep disturbances in advanced stage nonsmall-cell lung cancer patients. We, hereby, reported a statistical correlation between sleep quality and quality of life in our patients.